Neuroethics the ethical, legal, and societal impact of neuroscience.[article]. - Farah, Martha J
Advances in cognitive, effective, and social neuroscience raise a host of new questions concerning the ways in which neuroscience can and should be used. These advances also challenge our intuitions about the nature of humans as moral and spiritual beings. Neuroethics is the new field that grapples with these issues. The present article surveys a number of applications of neuroscience to such diverse arenas as marketing, criminal justice, the military, and worker productivity. The ethical, legal, and societal effects of these applications are discussed. Less practical, but perhaps ultimately more consequential, is the impact of neuroscience on our worldview and our understanding of the human person. - (from the author)
Keywords: Brain; Brain imaging; Enhancement; Free will; Privacy; Soul